2010
DOI: 10.1027/1864-9335/a000004
|View full text |Cite
|
Sign up to set email alerts
|

What You Did Only Matters if You Are One of Us

Abstract: Research has demonstrated that repeat offenders are generally punished more severely than first-time offenders. In the present article, we argue that this should particularly be true if the offender is a member of one’s own social category. A group of 86 students were told about a fellow student who hid books from the university library. The student was either an ingroup or an outgroup member and was either a first-time or a repeat offender. As expected, repeat ingroup offenders were more severely punished tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Ample research has systematically shown people's tendency to derogate deviant ingroup members as a means to protect the group from the threat that they pose to their identity (Abrams, Marques, Randsley de Moura, Hutchison, & Bown, 2006;Abrams, Rutland, Ferrell, & Pelletier, 2008;Marques & Paez, 1994;. Limited research exists, however, on how information about a harm-doers' group membership affects justice-related decisions (Braun & Gollwitzer, 2012;Brown et al, 2008;Gollwitzer & Keller, 2010;Gollwitzer & Van Prooijen, 2016;Van Prooijen & Lam, 2007), and no prior research exists on the motives underlying individuals' assignment of different types of punishment to ingroup versus outgroup transgressors. In Study 1, we tested the effect of a transgressor's group membership on observers' motives for punishment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ample research has systematically shown people's tendency to derogate deviant ingroup members as a means to protect the group from the threat that they pose to their identity (Abrams, Marques, Randsley de Moura, Hutchison, & Bown, 2006;Abrams, Rutland, Ferrell, & Pelletier, 2008;Marques & Paez, 1994;. Limited research exists, however, on how information about a harm-doers' group membership affects justice-related decisions (Braun & Gollwitzer, 2012;Brown et al, 2008;Gollwitzer & Keller, 2010;Gollwitzer & Van Prooijen, 2016;Van Prooijen & Lam, 2007), and no prior research exists on the motives underlying individuals' assignment of different types of punishment to ingroup versus outgroup transgressors. In Study 1, we tested the effect of a transgressor's group membership on observers' motives for punishment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has looked at the way people punish ingroup versus outgroup members (Braun & Gollwitzer, 2012;Brown, Gonz alez, Zagefka, Manzi, & Cehaji c, 2008;Gollwitzer & Keller, 2010;Gollwitzer & Van Prooijen, 2016;Van Prooijen & Lam, 2007). For instance, individuals tend to punish repeat ingroup offenders more severely than first-time ingroup offenders, whereas criminal history does not affect punitive reactions towards outgroup offenders (Gollwitzer & Keller, 2010). Similarly, Braun and Gollwitzer (2012) indicated that applying harsher punishments to ingroup rather than outgroup offenders often serves as a means by which ingroup members seek to protect their group's image.…”
mentioning
confidence: 99%
“…Subsequently, participants received the vignette including the group membership manipulation. The incident of norm deviance described a target person violating a formal social norm (for a similar manipulation, see Gollwitzer & Keller, 2010): A student selfishly hid an important book that many other students needed in the library. Due to enormous efforts of the library's employees, it was finally found, and the person hiding it could be traced.…”
Section: Methodsmentioning
confidence: 99%
“…Research into this black sheep effect (Marques & Yzerbyt, 1988) supports this claim, also noting that deviant in-group members are judged more harshly (but prototypical members less so) as a result. Further, in-group members who are repeat offenders are judged more harshly than those who have only committed deviant behavior occasionally, as greater frequency increases the threat to the group identity (Gollwitzer & Keller, 2010). Groups, whether online or offline, may even dispel deviant members (Birchmeier, Joinson, & Dietz-Uhler, 2005).…”
Section: Deviance In a Groupmentioning
confidence: 99%